Social Group Dynamics and Its Role in the Phenomenon of Bullying in Secondary Schools - Hamsah Hamsah,; Romi Mesra,; Darmawan Edi Winoto,; Marven Ajels Kasenda,; Delbert Mongan, (Technium Education and Humanities, 2024)
This study aims to analyze the dynamics of social groups and their role in the phenomenon of bullying in secondary schools. The main focus is to understand how interactions between groups, social norms, and hierarchical structures within groups affect the prevalence and forms of bullying. The method used is a qualitative approach with a systematic literature review. Relevant sources were identified through academic databases using specific keywords, then evaluated and analyzed using thematic analysis. The results of the study indicate that social group dynamics play a significant role in the phenomenon of bullying. Rigid hierarchical group structures, norms that support dominance, and intergroup competition tend to increase the risk of bullying. Conversely, groups with more egalitarian structures and inclusive values tend to show lower levels of bullying. The role of group leaders and bystanders was also found to be crucial in shaping responses to bullying. Contextual factors such as school transitions and the use of social media also influence the dynamics of bullying. Analysis using Social Identity Theory and Social Control Theory revealed that bullying is often rooted in the need to strengthen group identity and respond to weak social ties. These findings emphasize the importance of a holistic approach in bullying prevention and intervention efforts, which considers the complexity of group dynamics and the broader social context.